Acute Acalculous Cholecystitis: A Rare Presentation of Primary Epstein-Barr Virus Infection in Adults—Case Report and Review of the Literature - Zuhal Yesilbag; Asli Karadeniz; Fatih Oner Kaya (Case Reports in Infectious Diseases)
Primary Epstein-Barr virus (EBV) infection is almost always a self-limited disease characterized by sore throat, fever, and lymphadenopathy. Hepatic involvement is usually characterized by mild elevations of aminotransferases and resolves spontaneously. Although isolated gallbladder wall thickness has been reported in these patients, acute acalculous cholecystitis is an atypical presentation of primary EBV infection. We presented a young women admitted with a 10-day history of fever, nausea, malaise who had jaundice and right upper quadrant tenderness on the physical examination. Based on diagnostic laboratory tests and abdominal ultrasonographic findings, cholestasis and acute acalculous cholecystitis were diagnosed. Serology performed for EBV revealed the acute EBV infection. Symptoms and clinical course gradually improved with the conservative therapy, and at the 1-month follow-up laboratory findings were normal. We reviewed 16 adult cases with EBV-associated AAC in the literature. Classic symptoms of EBV infection were not predominant and all cases experienced gastrointestinal symptoms. Only one patient underwent surgery and all other patients recovered with conservative therapy. The development of AAC should be kept in mind in patients with cholestatic hepatitis due to EBV infection to avoid unnecessary surgical therapy and overuse of antibiotics.